INNOVATIVE CAPABILITY, INNOVATION STRATEGY AND MARKET ORIENTATION: AN EMPIRICAL ANALYSIS IN TURKISH SOFTWARE INDUSTRY - AKMAN, GÜLŞEN; YILMAZ, CENGIZ (International Journal of Innovation Management (ijim), 2008)
Innovation could be recognised as a key success factor in an increasingly competitive, global economy. The purpose of this paper is to examine the relations among market orientation, innovation strategy, innovative capability and innovation success in small and medium-sized business in developing countries. This study builds a model related to the most important factors that influence mostly innovative capability of firms, such as market orientation, technological orientation and innovation strategy. Then it examines the relationships between these factors and the innovative capability. A practical research was carried out in the Turkish software industry. Analysis, futurity and proactiveness dimensions of innovation strategy influence the innovative capability of software firms. Also, only customer orientation component of market orientation influences the innovative capability of the firms. Effects of other factors are not significant. Results of this study could lead to effective management of innovation for the software firms and benefits for the firms' managers.